Analisis Peran Digitalisasi Koperasi dalam Pengembangan Ekonomi Wilayah Perbatasan: Studi Kasus pada KSP CU Kasih Sejahtera Kota Atambua - Theresia Lorenza Jehalim Deo; Novi Theresia Kiak; Maria Indriyani H. Tiwu (Universitas Veteran Bangun Nusantara, 2024)
The purpose of this study is to analyze the role of cooperative digitalization in economic development in border areas, with a focus on the CU Kasih Sejahtera Savings and Loan Cooperative (SLC) in Atambua. This study uses a qualitative approach with a case study method, where data is collected through interviews, observations, and documentation. The number of informants in this study is 10 people, namely cooperative members and cooperative staff. The result of this study is that the implementation of digitalization in SLC CU Kasih Sejahtera has had a positive impact on economic development in border areas. Digitalization expands access to financial services for cooperative members, improves operational efficiency, and strengthens the connectivity of cooperatives with a wider financial network.